By‐Product‐Free Siloxane‐Bond Formation and Programmed One‐Pot Oligosiloxane Synthesis. (2nd February 2017) - Matsumoto, Kazuhiro; Sajna, Kappam Veettil; Satoh, Yasushi; Sato, Kazuhiko; Shimada, Shigeru
Abstract: Siloxane bonds are usually synthesized by condensation reactions, such as hydrolysis/dehydration and cross‐coupling reactions, in which the generation of by‐products during bond formation can not be avoided. We have developed a one‐pot sequence of iridium‐catalyzed silyl ester hydrosilylation and boron‐catalyzed rearrangement of the resulting disilyl acetals for the construction of siloxane bonds, in principle without the formation of any by‐products. Moreover, the programmed synthesis of tri‐, tetra‐, and pentasiloxanes was possible in a single flask by combining the above sequence of iridium‐catalyzed hydrosilylation and boron‐catalyzed rearrangement with a boron‐catalyzed cross‐coupling reaction. The obtained oligosiloxanes are difficult to synthesize selectively by other known synthetic procedures.